Respostas

2014-04-26T14:33:20-03:00
Acho que seria assim....


v=(m+7)i+(m+2)j+5k

|v| = raiz( (m+7)² + (m+2)² + 5² ) = raiz(38)

m² +14m +49 + m² + 4m + 4 + 25 = 38

2m² + 18m +40 =0

m² +9m +20 =0

m= -5 ou m= -4

2.Dados os pontos A(1,0,-1),B(4,2,1) e C(1,2,0)

vetor AB = (4-1 , 2-0 , 1-(-1) ) = (3 , 2 , 2)
vetor BC = ( 1 -4 , 2 -2 , 0-1) = (-3 , 0 , -1)

m.AB = (3m ,2m ,2m)

v= mAC+BC = (3m-3 , 2m+0 , 2m-1)

|v| = raiz( (3m-3)² + (2m)² + (2m -1)² ) = 7 ... elevando ao quadrado...
(3m-3)² + (2m)² + (2m -1)² =49

9m² - 18m +9 +4m² + 4m² -4m +1 =49

17m² - 22m -39 =0

m=( 22+-56)/2.17

m= 78/2.17 = 39/17 ou m= -1

3.Dados os pontos A(3,m-1,-4) e B(8,2m-1,m)

AB =( 8-3 , (2m-1) - (m-1) , m -(-4) ) = ( 5 , m , m+4)

vetor AB = ( 5 , m , m+4)

|AB| = raíz ( 5² + m² + (m+4)² ) = raíz (35)

25 + m² + m² + 8m +16 = 35

2m² + 8m +6 =0

m² + 4m + 3 =0

m= -3 ou m= -1
5 3 5